Self-objectification, weight bias internalization, and binge eating in young women: Testing a mediational model. (March 2018) - Mehak, Adrienne; Friedman, Aliza; Cassin, Stephanie E.
Highlights: Internalized weight-related social pressures correlate with negative affect. Young women may engage in binge eating to regulate body-focused negative affect. Negative affect mediated the relation between internalization and binge eating. Appearance anxiety and body shame emerged as significant explanatory mechanisms. Body shame is a stronger mediator than appearance anxiety. Abstract: Self-objectification and weight bias internalization are two internalization processes that are positively correlated with binge eating among young women. However, the mechanisms underlying these relationships are understudied. Consistent with objectification theory, this study examined appearance anxiety and body shame as mediators between self-objectification, weight bias internalization and binge eating. Female undergraduates ( N = 102) completed self-report measures of self-objectification, weight bias internalization, appearance anxiety, body shame, and binge eating. Results indicated that women who self-objectified and internalized negative weight-related attitudes reported greater binge eating ( rs = .43 and rs = .57, respectively) and these associations were mediated by the combined effects of body shame and appearance anxiety. The contrast between the two mediators was also significant, such that body shame emerged as a stronger mediator within both mediational models. Results demonstrated that these internalization processes contribute to negative affect in young women, which may in turn lead to binge eating.